2002
DOI: 10.1016/s0039-3681(02)00033-x
|View full text |Cite
|
Sign up to set email alerts
|

Why did we think we dreamed in black and white?

Abstract: In the 1950's, dream researchers commonly thought that dreams were predominantly a black-and-white phenomenon, although both earlier and later treatments of dreaming presume or assert that dreams have color. The first half of the twentieth century saw the rise of black-and-white film media, and it is likely that the emergence of the view that dreams are black-and-white was connected with this change in media technology. If our opinions about basic features of our dreams can change with changes in technology, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
1
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(26 citation statements)
references
References 30 publications
0
22
1
3
Order By: Relevance
“…Based on a review of historical studies on color in dreams, he found evidence for “an arc of opinion: before scientific psychology, a consensus or assumption that dreams are colored; divided opinions into the early twentieth century; a consensus that dreams typically have little color from about 1930 to 1960; and then a sudden overturning of that consensus in the 1960s” (Schwitzgebel, 2011, p. 5; cf. Schwitzgebel, 2002). …”
Section: Skepticism About Dream Reportingmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on a review of historical studies on color in dreams, he found evidence for “an arc of opinion: before scientific psychology, a consensus or assumption that dreams are colored; divided opinions into the early twentieth century; a consensus that dreams typically have little color from about 1930 to 1960; and then a sudden overturning of that consensus in the 1960s” (Schwitzgebel, 2011, p. 5; cf. Schwitzgebel, 2002). …”
Section: Skepticism About Dream Reportingmentioning
confidence: 99%
“…Schwitzgebel repeatedly (2002; 2011; Schwitzgebel et al, 2006) describes the possibility of a change in dreaming as opposed to a change in dream reporting as unlikely, defending the claim that either all or a certain group of subjects have mistaken opinions about the occurrence of color in their dreams. The deeper point, however, is that because all three interpretations are possible, and given that none of them can be ruled out at the outset, this finding itself undermines, or so it might seem, the transparency assumption with respect to reports of colored dreaming.…”
Section: Skepticism About Dream Reportingmentioning
confidence: 99%
“…David Davies and Andrew Fisher independently pointed out that in the later research, unlike the earlier research, people were woken from REM sleep, which casts doubt on the comparability of the result. Schwitzgebel has other data—including replicating a 1942 study—which convinces me that, nonetheless, there is an interesting systematic difference between earlier and later reports (, 651).…”
mentioning
confidence: 78%
“…It would be odd to suppose that whether she dreamed about them in color would be depend on what she sees in the cinema or on the television screen. (, 653)…”
Section: Dreaming In Black and Whitementioning
confidence: 99%
“…Therefore, the influence of how we accept certain content is greater than how and at what time the information is provided. This is because there is a difference in the level of prior knowledge or information that every individual possesses (Schwitzgebel 2002).…”
Section: Media Richnessmentioning
confidence: 99%